ANALISA RAMALAN PRODUKSI LEMARI PAKAIAN PADA UD. MEBEL FILKIN DESA WAYAME - Janet Beatric Tutuarima; Ashwin Siahainenia; Febiola Matuankotta (P3M Politeknik Negeri Ambon, 2026)
The purpose of this study was to calculate and analyze the forecast of wardrobe production at Filkin Furniture from January – October 2023. Filkin Furniture is a company engaged in furniture, namely the manufacture and sale of wardrobes according to consumer demand based on the order data obtained. The analysis used in this study is Linear Trend Analysis using the equation formula Y = a + bx and to determine the accuracy of the forecast that has been known using Standard Error of Estimate Analysis (Error Rate). The results of the calculation of the Linear Trend Analysis can be seen that the forecast of wardrobe production in UD. Filkin Furniture is 6 units in December 2023, 6 units in January 2024, and 6 units of wardrobes in February 2024. The Standard Error of Estimate shows that the error rate in production forecasting is as much as 1 wardrobe, so there is a possibility of errors in making this forecast. Thus, it can be seen that the production forecast for the three months is at the same number, namely production of 6 units with a standard error of 1 unit; this can happen because the production data in the previous month has a trend that tends to be the same, resulting in the results of the trend forecasting also being the same. Keywords: Forecasting Analysis